Urbanization and land surface temperature in Kuantan: A geographic information systems-based analysis of urban heat island dynamics - Zhai, Wenxin; Syarifuddin, Misbari; Doh, Shu Ing (Penerbit UMP, 2025)
Rapid urbanization and industrial development in Kuantan, Malaysia, have significantly contributed to the intensification of the Urban Heat Island effect. In Kuantan, the urban heat island (UHI) effect has led to increased surface temperatures, especially in densely built areas, contributing to higher energy consumption for cooling. The loss of green spaces due to rapid urban expansion and industrial activities has further intensified heat retention, worsening thermal discomfort for residents. This study investigates the spatial and temporal dynamics of UHI in Kuantan using Landsat satellite images and Geographic Information System techniques. Land Surface Temperature (LST) data and the Normalized Difference Vegetation Index (NDVI) were analyzed to evaluate the relationship between urban expansion, vegetation cover, and surface temperature over a decade. The findings revealed a notable increase in UHI intensity, with urbanized areas experiencing higher LST compared to vegetated zones. Between 2005 and 2024, the Urban Heat Island Intensity (UHII) in Kuantan increased by approximately 5°C. Areas with reduced vegetation cover, such as industrial and commercial zones, demonstrated heightened heat accumulation, while green spaces effectively mitigated urban heat. These results underscore the critical importance of integrating green infrastructure into urban planning to address the challenges posed by UHI. The study provides actionable insights for sustainable urban development strategies in tropical cities like Kuantan.